Răspuns :
Răspuns:
Explicație pas cu pas:
x/√3-2y/√3=4
3x/√2+y/√3=5 notam=x/√2=t si y/√3=u
t-2y=4 t-2y=4
3t+u=5 (2) 6t+2y=10
...........................
7t=14 t=2 u=5-3×2=-1
x/√2=2 x=2√2
y/√3=-1 y=-√3
[tex]\it \begin{cases}\it\dfrac{x}{\sqrt2}- \dfrac{2y}{\sqrt3}=4\\ \\ \\ \it \dfrac{3x}{\sqrt2}+\dfrac{y}{\sqrt3}=5|_{\cdot2}\end{cases} \Rightarrow \begin{cases}\it\dfrac{x}{\sqrt2}- \dfrac{2y}{\sqrt3}=4\\ \\ \\ \it \dfrac{6x}{\sqrt2}+ \dfrac{2y}{\sqrt3}=10\end{cases}\\ \\ \\ .\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ --------- \\ .\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \dfrac{7x}{\sqrt2}.\ \ \ \ \ \ \ \ =14[/tex]
[tex]\it\ \dfrac{7x}{\sqrt2}=14|_{:7} \Rightarrow \dfrac{x}{\sqrt2}=2 \Rightarrow x=2\sqrt2[/tex]
Înlocuim valoarea lui x în prima ecuație și obținem:
[tex]\it \dfrac{2\sqrt2}{\sqrt2}-\dfrac{2y}{\sqrt3}=4 \Rightarrow 2-4=\dfrac{2y}{\sqrt3} \Rightarrow -2=\dfrac{2y}{\sqrt3}|_{:2} \Rightarrow-1=\dfrac{y}{\sqrt3}\Rightarrow y=-\sqrt3[/tex]